A technique for determination of natural stresses in rock masses by surface deformation using satellite navigation systems - Zubkov, A. V.; Sentyabov, S. V.; Selin, K. V. (Litosfera (Ekaterinburg. Online), 2019)
Research subject . The relative deformation of rock masses, which was obtained in the Urals at depths below500 m, i.e. below the zone of massif disintegration, through the use of traditional geodetic measurement methods, allows correction of the results of determining the massif basis to obtain its true value. Materials and methods . A method for determining natural stresses was developed on the basis of a physical law stating that the natural stress state of the Earth’s crust is formed as a result of the application of stress fields due to the gravitational and tectonic forces of the Earth, as well as astrophysical forces caused by physical processes in space. Results . The Earth’s stress state is largely formed by the contribution of the gravitational and astrophysical components. The value of the astrophysical component varies in time with a cycle of up to twelve years and reaches tens of MPa at depths of more than500 meters, while the tectonic component, on average, does not exceed the value of 1 MPa. The experimentally obtained deformation of the Earth’s crust, i.e. lithospheric plates in the Pacific, Indian and Atlantic oceans, as well as continental plates inAsia and the Urals, indicates their identical and volumetric deformation in all regions of the world. Conclusion s. On the basis of experimental data on a cyclic change in the linear parameters of the Earth’s crust, it is concluded that satellite navigation systems determine geographical coordinates with an error. A significant increase in the astrophysical component of stresses over a short period of 2-3 years in the eleven-year cycle is the main reason for the activation of earthquakes and the destruction of structures constructed in the rock environment.